Sustainable supply chain management in the food Industry (2019)
The article presented below has the objective of identifying the main factors that affect the sustainable supply chain management in the international food industry. For the methodological process, it was implemented the technique of content analysis of scientific documents published between 2006 and 2017 in the databases of SCOPUS, ISI Web Of Science, Science Direct and JSTOR. Among the findings are the existence of factors such as senior management, business strategy, organizational structure, measurement and monitoring systems for sustainability, environmental awareness, physical plant design, dynamic capabilities, policies and regulations, supplier management and customer attitude as part of the key elements for the sustainable supply chain management in food industry companies. In addition, the results allow us to recognize this approach as emerging, in which the need to develop networking among the actors involved in production is highlighted.